ENGLISH PUBLIC UTILITY CONCERNS AND STATUTORY RESERVE FUNDS. - Taggart, P. (The Accounting Review, 1930)
Abstract Companies formed under the English laws may be either Joint Stock Companies, that is formed under the Companies Act, or Statutory Companies, generally formed under a Private Act of Parliament incorporating the clauses of the Companies Clauses Act and such other Acts as may be applicable. In the case of ordinary Companies not having public utility characteristics, the legislature has tended to leave the Companies themselves to adjust questions of finance as between the shareholders, on the one side, and the customers, on the other side, as normally the field of supply is open for the operations of competitors to the advantage and protection of the public. In the case of public utility concerns, however, the same degree of possible competition is not available, so that the "undertakers" are not unreasonably restricted as to dividends in the interests of the consumers who have to pay the tariffs for their supply. The mere regulation of dividends, however, would not be sufficient protection for consumers unless limitations were also placed upon the accumulation of surplus profits.